Forest and land fires in Pelalawan District, Riau, Indonesia: Drivers, pressures, impacts and responses - HESTI LESTARI TATA; BUDI HADI NARENDRA; MAWAZIN MAWAZIN (Society for Indonesian Biodiversity, 2018)
Tata HL, Narendra BH, Mawazin. 2018. Forest and land fires in Pelalawan District, Riau, Indonesia: Drivers, pressures, impacts and responses. Biodiversitas 19: 544-551. Pelalawan District of Riau Province, Indonesia was one of the districts most damaged by fire in 2015. Analysis of factors driving the fires, of pressures arising from the fires and of responses to the fires in Pelalawan District was conducted using two approaches: semi-structured interviews regarding social and policy aspects, and analysis of biophysical factors such as soil properties and spatial data. Results showed that forest functions (i.e. the functions served by different forest types) was positively related to hotspot density (R2=0.9868), while distance to nearest road less affected hotspot distribution (R2=0.1612). Multiple regression analysis of the relationship between hotspots density and four variables resulted in the following model: Y = 0.005384 + 0.000021 Soil Type + 0.000019 Distance to Road + 0.000038 Forest Functions + 0.000017 Land Use type. The pressures were expansion for agriculture, plantation and forest encroachment. Despite many negative impacts of fire, the burning practice on peatland could improve the pH and peat soil fertility (particularly ash and P contents). As a response to fire, a standard operational procedure for forest- and land-fire prevention was launched by the Governor of Riau Province in late 2015. A comprehensive and integrated policy package for forest and land fire prevention and control should include a social dimension in order to effectively reduce fire risk in the district.